Effect of effluent and fertilizer application on growth and yield of sugarcane - Singh, VP; Singh, A; Singh, VP; Singh, J; Rawat, KS; Kumar, R (Annals of Agricultural Research, 2014)
A field experiment was conducted at research farm of Jubilant Organosys Ltd., Gajraulla, University of Agriculture & Technology, Modipuram, Meerut ,U.P. in collaboration with G.B. Pant University of Agriculture & Technology, Pantnagar to investigate the response of effluent with and without fertilizer application on growth, yield attributes and yield of sugarcane (var. CoS 767). The levels of irrigations were viz., irrigation with fresh water, pre-sowing irrigation of undiluted effluents, one irrigation with 1:3 dilution and two irrigation with 1:4 dilution and the fertilizers levels were viz., without fertilizers and half dose of the recommended fertilizer (75:30:20 NPK) in split plot design. The highest cane yield (104.83 t ha-1) was found in the treatment receiving two irrigations with 1:4 dilution along with 50% recommended dose of fertilizers. Treatment receiving two irrigation with 1:4 dilution of effluent without fertilizer gave almost similar yield (99.94 t ha-1) to the treatment receiving one irrigation with 1:3 dilution along with 50% recommended dose of fertilizer indicating that, almost 50% of NPK have been saved. Again, the treatment receiving one irrigation with 1:3 dilution without fertilizer gave similar yield (94.11 t ha-1) as that of pre-sown undiluted with 50% recommended dose of fertilizer (95.55 t ha-1), showed saving of 50% of recommended dose of NPK.